Marketing strategy formulation for innovative product development process - Zemlickienė, Vaida; Maditinos, Dimitrios Ioannis (Business: Theory and Practice, 2012)
The scientific literature widely considers the new product development (NPD) process. Innovation process influencing NPD process brings for the product an exceptional value which stimulates market demand of these products. However to create a successful new product is not easy. Scholars of management, politicians and economists acknowledge the advantages of new products and market power, but the development of these products is a problematic and long-term process that requires considerable time and financial costs, which often does not receive the return. Scholars state that problems are related to marketing. Based on these research results, the article concentrates on the marketing strategy formulation for a NPD process. The aim of this study is to gather, research and generalize recent scientific literature in order to provide conclusions, related to the marketing strategy formulation for the NPD. Implementing the aim of this study, most of the chaos was caused by fact that NPD process, innovation process and the research commercialization process are interrelated, and problem-solving has particular features in common. In order to clarify the relationship between these processes, a comparison of these processes and definitions was carried out. In analysis of NPD process, the limits of research were set - the process was analysed from the initial product design phase and was completed with the product introduction to the market.